Buenas prácticas de comunicación interna en la pandemia en una empresa de servicios: un acercamiento a la comunicación bajo el enfoque de procesos - Oliva Tamayo, Andrea (2023)
The COVID-19 pandemic crisis that disrupted business companies produced immeasurable challenges for management in companies. To address the crisis, one of the functions they resorted to was internal communication which allowed employees to stay connected to their work and the organization in the new remote environment, thus helping to mitigate the impact of work isolation on the workforce. This article examines the internal communication best practices deployed by a technology services company in Peru during the pandemic, a task in which we applied a process-oriented approach. During the analysis, we identified -in addition to the elements that triggered the processes- the use of online channels, the level of employee satisfaction with the information they received, and the role of managers in internal communication within the context of remote work. The research employed a mixed methodology of surveys and interviews, along with the application of the process model for each best practice. The conclusions of the article suggest that the contributions of internal communication to the organization depend not only on the variety of activities, channels, and communication pieces developed but also on the appropriate use of resources, the transformations performed with them, and the results that served the organization´s purposes.